Administration of Buddhist Based Schools Under Nonthaburi Elementary Educational Service Area Office 2 - Tawee, Thanawat; Phrakruchairattanakon,; Silpanilmalaya, Anake (Academic Journal of Mahamakut Buddhist University Roi Et Campus, 2020)
The objectives of the research article were 1) to study administration of Buddhist based schools, 2) to compare the opinions towards the administration of Buddhist based schools of administrators and teachers responsible for the administration of Buddhist based school project, 3) to collect recommendations for administration of Buddhist based schools under Nonthaburi Elementary Educational Service Area Office 2. The samples from 80 administrators and teachers responsible for administration. The data used for collecting data were frequency, percentage, standard deviation, and t-test and F- test with using software package. The results of the research showed that : 1.Administration of the Buddhist based schools under Nonthaburi elementary educational Service Area 2 has a high average in overall. 2. Statements on comparison of the opinions towards administration of the Buddhist based schools of administrators and teachers responsible for the administration of the Buddhist based schools project under Nonthaburi elementary education service area 2, including to the gender, education and work experience were no difference. 3. Recommendations for administration of the Buddhist based schools under Nonthaburi elementary education service area 2 found that physical, administrators, teachers and students should achieve moral and ethical development. Students should be encouraged in Basic activities on lifestyles to participate in Buddhist activities organized by various organizations, organized an exhibition of students' Buddhist works, regarding teaching and learning, administrators and teachers should integrate Buddhist principles, including knowledge, in organizing learning units for all groups. Arrange the environment and interaction with self-development to increase knowledge and ability, yearning for knowledge, interest in education for self-improvement so as to management. The executives should encourage their operations by adhering to rules, regulations, and orders in order to create effective work.